Whole-Genome Linkage Scan Combined With Exome Sequencing Identifies Novel Candidate Genes for Carotid Intima-Media Thickness - Vojinovic, Dina; Kavousi, Maryam; Ghanbari, Mohsen; Brouwer, Rutger W. W.; van Rooij, Jeroen G. J.; van den Hout, Mirjam C. G. N.; Kraaij, Robert; van Ijcken, Wilfred F. J.; Uitterlinden, Andre G.; van Duijn, Cornelia M.; Amin, Najaf (Frontiers in Genetics, 2018)
Carotid intima-media thickness (cIMT) is an established heritable marker for subclinical atherosclerosis. In this study, we aim to identify rare variants with large effects driving differences in cIMT by performing genome-wide linkage analysis of individuals in the extremes of cIMT trait distribution (> 90th percentile) in a large family-based study from a genetically isolated population in the Netherlands. Linked regions were subsequently explored by fine-mapping using exome sequencing. We observed significant evidence of linkage on chromosomes 2p16.3 (rs1017418, heterogeneity LOD (HLOD) = 3.35), 19q13.43 (rs3499, HLOD = 9.09), 20p13 (rs1434789, HLOD = 4.10) and 21q22.12 (rs2834949, HLOD = 3.59). Fine-mapping using exome sequencing data identified a non-coding variant (rs62165235) in PNPT1 gene under the linkage peak at chromosome 2 that is likely to have a regulatory function. The variant was associated with quantitative cIMT in the family-based study population (effect = 0.26, p-value = 0.013). Furthermore, we identified several genes under the 21q22 linkage peak highly expressed in tissues relevant for atherosclerosis. To conclude, our linkage analysis identified four genomic regions significantly linked to cIMT. Further analyses are needed to demonstrate involvement of identified candidate genes in development of atherosclerosis.